Developing and validating a web-based learning environment for helping 6th grade students appreciate subjectivity and uncertainty in science - Constantinou, Constantinos P.; Michael, Georgia; Papadouris, Nicos; Kyza, Eleni A. (My University, 2010)
This study reports on the development and research validation of a web-based learning environment (LE) for helping students, ages 12-14, to appreciate uncertainty and subjectivity in science. The environment was implemented once and the research results are used for revising it to better address the learning objectives. Results in relation to students' understanding of subjectivity and possible emerging modifications of the LE are discussed. ISLS.
Keywords: Computer aided instruction; Learning objectives; Research results; Research validation; Web-based learning environment; E-learning; Online systems; Students